Hugo Pecse (1900 - 1969) Semblance - Fernández Dávila, Luis (1995)
Master Hugo Pecse remember, teaching classes on leprosy. His voice was slow, is somewhat off. And in the silence of the classroom and respect for his audience his lesson flowed easily and extraordinary clarity.